ECOLOGY AND CONTROL OF EYE FLIES SIPHUNCULINA SPP. ( CHLOROPIDAE : DIPTERA ) - T. V. SATHE; DIVYA JADAV (International Journal of Pharma and Bio Sciences, 2014)
Kolhapur district of Maharashtra, India is high populated, leading in agriculture and industries and very rich in biodiversity. High rainfall (6000 mm) and decaying organic bodies of plants and animals prevail eyeflies Siphunculina spp. (Chloropidae: Diptera) in the region from February third week to September third week every year. Siphunculina spp. have the forensic and medical importance. Extremely large aggregations of eyeflies were common in areas of loose sandy soils and decaying organic matters in and around city Kolhapur and its tahasils. The high concentrations of flies were a great nuisance to humans and animals. Specially, agricultural, recreational, institutional and tourist areas. Eye flies were responsible for transmitting acute conjunctivitis, "pink eye" and several other diseases to humans and live stock. The flies were attracted to fluids secreted by eyes, nose, ears, wounds and excrements of humans and other animals. Four species of the genus Siphunculina namely S. funicola, S. ulceri, S. faciata and S. striatata were prevalent in Kolhapur region. Out of which S. funicola was dominant over others and S. ulceri was moderate. S. funicola and S. ulceri completed their life cycles within 2 weeks and 3 weeks respectively. Disposal of aggregation sources of flies and decaying organic matters and treating such breeding places with 0.03/DDVP/malathion /Azadirachtin can control the eyeflies.